Morphological changes in a low-energy backbarrier - Carrasco, Ana Rita (2017)
Profile characteristics of low energy sandy beaches include narrow foreshores that are often steep, with reflective swash zones. Seaward of the foreshore a low gradient terrace is generally present, acting as a wave energy filter. Low magnitude changes are usually associated to this type of environments, either cross-or longshore. To examine the short- (between months) and medium-term (from months to years) morphological changes at Ancão backbarrier (Ria Formosa), data from monthly cross-shore surveys was used. The degree of morphological mobility was given by the volumetric variability within specific morphologic units (foreshore, tidal flat and sand spit) and through the analysis of three cross-shore sections. The results show low medium-term variability, not seasonally distributed, and without a direct connection to changes on average wind intensity. The three morphologies are not interdependent and do not show a clear relation on sediment exchanges between them. Low intensity short-term changes are however present, which seem to be related with net sediment adjustments.